Gender Performance and Spatial Negotiation in the Neo-Victorian Novel - Pettersson, Lin Elinor (Textos Mínimos, 2014)
The present volume examines Judith Butlers concept of gender performance in Angela Carters _Nights at the Circus_ (1984), Sarah Waterss ¬_Tipping the Velvet_ (1998) and Peter Ackroyds _Dan Leno and the Limehouse Golem_ (1994). All of them depict how female performers make use of the stage to expose gender identity as an act performance and in doing so they destabilise the public/private dichotomy.